Saccharina japonica Ethanol Extract Ameliorates Depression/Anxiety-Like Behavior by Inhibiting Inflammation, Oxidative Stress, and Apoptosis in Dextran Sodium Sulfate Induced Ulcerative Colitis Mice - Dong, Xiufang; Lu, Kuan; Lin, Pengcheng; Che, Hongxia; Li, Hongyan; Song, Lin; Yang, Xihong; Xie, Wancui (Frontiers in Nutrition, 2021)
Saccharina japonica is a common marine vegetable in East Asian markets and has a variety of health benefits. This study was focused on the anti-depressant/anxiety effects of Saccharina japonica ethanol extract (SJE) on dextran sodium sulfate (DSS)-induced mice and its potential mechanism in their brain. Male C57BL/6 mice were treated with mesalazine and various doses of SJE (1, 2, and 4 g/kg body weight) for two weeks, followed by DSS treatment at the second week. The DSS-induced mice showed depression/anxiety-like behavior, which included shorter path length in the open field test and longer immobility time in the tail suspension test. L-SJE alleviated the depression-like behaviors. In the DSS-induced mice, reduced synaptic plasticity activated microglia, increased proinflammatory cytokines, decreased anti-inflammatory cytokine, and increased expression levels of Toll-like receptors-4, nuclear factor kappa-B, NOD-like receptors 3, apoptosis-associated speck-like protein, and Caspase-1 were observed, most of which were alleviated by SJE treatment. Furthermore, all the SJE groups could significantly enhance superoxide dismutase activity, while the L-SJE treatment decreased the contents of malondialdehyde, and the H-SJE treatment inhibited apoptosis. All these results showed that the SJE might serve as a nutritional agent for protecting the brain in ulcerative colitis mice.